A comparative evaluation of visual characteristics and gross fog of standard occlusal films and occlusal films prepared from extraoral films with intensifying screens - Asieh Zamani Naser; Aminollah Safari; Nasim Jafari Pozveh; Nastaran Farhadi; ladan Khorrami (Isfahan University of Medical Sciences, 2013)
Introduction: Due to ever-increasing need for diagnostic radiographs in dentistry, it is necessary to observe techniques to minimize the absorbed patient dose. The aim of this study was the comparative evaluation of inherent visual characteristics such as contrast and density and the gross fog of standard occlusal films with those of occlusal films taken with intensifying screens.Materials and Methods: In this experimental research, standard occlusal films and occlusal films prepared by cutting extraoral films to the size of occlusal films and placing them between intensifying screens were used. After determination of the most appropriate exposure time and maximum kVp and mA, radiographs were taken from one step wedge and processed using the same condition. A total of 25 radiographs were taken from each of the two film types and then the radiographs underwent densitometry at similar points. In order to evaluate the gross fog, densitometry was carried out at 5 similar points on one unexposed film from each type. Data were analyzed using SPSS 11.5 software and Mann-Whitney test (α = 0.05).Results: Based on the results of this study, the density of the standard occlusal film was more than that of the occlusal film with intensifying screens (p value < 0.001). The contrast of the film with intensifying screens was more than that of the standard occlusal film (p value < 0.001). The gross fog of the film with intensifying screens was less than that of the standard occlusal film (p value = 0.006).Conclusion: Occlusal films with intensifying screens have higher contrast and lower gross fog and density, but in the diagnostic range, in comparison with standard occlusal films; therefore, films with intensifying screens are recommended because they decrease patient absorbed dose by decreasing exposure time. Key words: Densitometry, Radiography, X-ray intensifying screens